Clostridium difficile infection - Stephen A. Geller; Fernando Peixoto Ferraz de Campos (University of São Paulo, 2014)
Clostridium difficile infection (CDI) is a significant and increasing medical problem, surpassing methicillin-resistant Staphylococcus aureus as the most common hospital-onset or facility-associated infection, and a key element in the challenging battle against hospital-acquired infections. This Gram-positive, anaerobic, spore-forming colonizes the intestinal tract after antibiotics have altered the normal intestinal flora.